KONSTRUK INDEPENDENSI MANUSIA DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Zainullah, Zainullah (Universitas Islam Lamongan, 2017)
Independence (freedom) is not something that has been made, but the possibility given and the value to be won by overcoming a number of determinism. Independence means that humans are needed as subjects. Man who has freedom of will that can not determine his will, because the ability of human reason is limited. In the world of education must also accept and be able to liberate human beings, because authentic education is education that requires freedom, which always gives opportunities to learners as widely as possible so that can mensentisekan the rich, admitted or not Islamic education has the goal of creating human beings capable of using the mind As the source of his thinking to achieve the ultimate truth. This type of research is literature review, which displays the argumentation of scientific reasoning that describes the results of literature review and the results of the researcher's analysis of Human Independence in Perspectives of Islamic Education Philosophy. This kind of study includes or explores the ideas of related propositions and should be supported by data or information obtained from the literature. With the foundation of qualitative and rationalistic philosophy. As a result shows that human independence is freedom and liberation from the shackles of material and kerohaniaan which is a structural and cultural oppression, both political, legal, economic and so forth. The construct of human independence and its implications in Islamic education is an attempt to cultivate a critical, creative and constructive atmosphere in developing human potential to meet the challenges of the times.Keywords: Human Independence Constructs, Implications of Independence in Islamic Education